KAJIAN KEMAMPUAN LAHAN PADA USAHATANI LAHAN KERING BERBASIS TEMBAKAU DI SUB-DAS PROGO HULU - Jaka Suyana; Naik Sinukaban; Bunasor Sanim; M.Yanuar J Purwanto (Faculty of Agriculture, Universitas Sebelas Maret, 2010)
Title : The Study of Land Capability on Tobacco-Based Upland Farming at Progo Hulu Sub-Watershed. The recent and also the future problems for Indonesian concerning with agricultural environment resources are land degradation and water resources restrictiveness. Agricultural technique without awareness to concerning to soil and water conservation principles on steep and high rainfall area had caused severe erosion and land degradation at upland area of Progo Hulu sub-watershed. Land Degradation that promoted by erosion at Progo Hulu sub-watershed contributed negative effects at on-site and out-site area. The land capability analysis shows that tobacco-based farming system at Progo Hulu sub watershed dominated by class IV (3,624.93 ha; 49.00%), followed with class VI (2,488.82 ha; 33.64%), class III (697.99 ha; 9.43%), class V (450.73 ha; 6.09%), and class VII (136.06 ha; 1.84%). The main resistance factors are slope and erosion for class III; erosion, slope and surface rocks for class VI; and slope for class VII. Keywords: land capability, Progo Hulu Sub-watershed